Executive Functions and Prosodic Abilities in Children With High-Functioning Autism - Filipe, Marisa G.; Frota, Sónia; Vicente, Selene G. (Frontiers in Psychology, 2018)
Little is known about the relationship between prosodic abilities and executive function skills. As deficits in executive functions and prosodic impairments are characteristics of autism, we examined how executive functions are related to prosodic performance in children with high-functioning autism (HFA). Fifteen children with HFA (M =7;4 years; SD = 1.12), matched to 15 typically developing peers on age, gender, and non-verbal intelligence participated in the study. The Profiling Elements of Prosody in Speech-Communication (PEPS-C) was used to assess prosodic performance. The Children's Color Trails Test (CCTT-1, CCTT-2, and CCTT Interference Index) was used as an indicator of executive control abilities. Our findings suggest no relation between prosodic abilities and visual search and processing speed (assessed by CCTT-1), but a significant link between prosodic skills and divided attention, working memory/sequencing, set-switching, and inhibition (assessed by CCTT-2 and CCTT Interference Index). These findings may be of clinical relevance since difficulties in executive functions and prosodic deficits are characteristic of many neurodevelopmental disorders. Future studies are needed to further investigate the nature of the relationship between impaired prosody and executive (dys)function.